Current Molecular Epidemiology of Methicillin-Resistant Staphylococcus aureus in Elderly French People: Troublesome Clones on the Horizon - Rondeau, Claire; Chevet, Guillaume; Blanc, Dominique S.; Gbaguidi-Haore, Houssein; Decalonne, Marie; Dos Santos, Sandra; Quentin, Roland; van der Mee-Marquet, Nathalie (Frontiers in Microbiology, 2016)
Objective: In 2015, we conducted at 44 healthcare facilities (HCFs) and 21 nursing homes (NHs) a 3-month bloodstream infection (BSI) survey, and a 1-day prevalence study to determine the rate of carriage of methicillin-resistant Staphylococcus aureus (MRSA) in 891 patients and 470 residents. We investigated the molecular characteristics of the BSI-associated and colonizing MRSA isolates, and assessed cross-transmission using double-locus sequence typing and pulsed-field gel electrophoresis protocol. Results: The incidence of MRSA-BSI was 0.040/1000 patient-days (19 cases). The prevalence of MRSA carriage was 4.2% in patients (n = 39) and 8.7% in residents (n = 41) (p < 0.001). BSI-associated and colonizing isolates were similar: none were PVL-positive; 86.9% belonged to clonal complexes 5 and 8; 93.9% were resistant to fluoroquinolones. The qacA/B gene was carried by 15.8% of the BSI-associated isolates [3/3 BSI cases in intensive care units (ICUs)], and 7.7% of the colonizing isolates in HCFs. Probable resident-to-resident transmission was identified in four NHs. Conclusion: Despite generally reassuring results, we identified two key concerns. First, a worryingly high prevalence of the qacA/B gene in MRSA isolates. Antisepsis measures being crucial to prevent healthcare-associated infections, our findings raise questions about the potential risk associated with chlorhexidine use in qacA/B+ MRSA carriers, particularly in ICUs. Second, NHs are a weak link in MRSA control. MRSA spread was not controlled at several NHs; because of their frequent contact with the community, conditions are favorable for these NHs to serve as reservoirs of USA300 clone for local HCFs.